A study of association between common variation in the growth hormone-chorionic somatomammotropin hormone gene cluster and adult fasting insulin in a UK Caucasian population - Freathy, Rachel M (BioMed Central, 2006)
BACKGROUND: Reduced growth during infancy is associated with adult insulin resistance. In a UK Caucasian cohort, the CSH1.01 microsatellite polymorphism in the growth hormone-chorionic somatomammotropin hormone gene cluster was recently associated with increases in adult fasting insulin of approximately 23 pmol/l for TT homozygote males compared to D1D1 or D2D2 homozygotes (P = 0.001 and 0.009; n = 206 and 92, respectively), but not for females. TT males additionally had a 547-g lower weight at 1 year (n = 270; P = 0.008) than D2D2 males. We sought to replicate these data in healthy UK Caucasian subjects. We genotyped 1396 subjects (fathers, mothers and children) from a consecutive birth study for the CSH1.01 marker and analysed genotypes for association with 1-year weight in boys and fasting insulin in fathers. RESULTS: We found no evidence for association of CSH1.01 genotype with adult male fasting insulin concentrations (TT/D1D1 P = 0.38; TT/D2D2 P = 0.18) or weight at 1 year in boys (TT/D1D1 P = 0.76; TT/D2D2 P = 0.85). For fasting insulin, our data can exclude the previously observed effect sizes as the 95 % confidence intervals for the differences observed in our study exclude increases in fasting insulin of 9.0 and 12.6 pmol/l for TT relative to D1D1 and D2D2 homozygotes, respectively. Whilst we have fewer data on boys' 1-year weight than the original study, our data can exclude a reduction in 1-year weight greater than 557 g for TT relative to D2D2 homozygotes. CONCLUSION: We have not found association of the CSH1.01 genotype with fasting insulin or weight at 1 year. We conclude that the original study is likely to have over-estimated the effect size for fasting insulin, or that the difference in results reflects the younger age of subjects in this study relative to those in the previous study.